High prevalence of cervical spine pain and injuries among breaking dancers: A cross-sectional study with comparison to rugby and proposal for a primary prevention protocol - Dufour, T.; Laurin, C. (Journal of Dance Medicine & Science, 2026)
Introduction: Breaking is a high-risk discipline for the cervical spine, with movements such as the halo and headspin exposing dancers to significant stresses. Epidemiological studies highlight a high incidence of neck pain and injuries among breakers, while primary prevention remains limited due to a lack of data.